Effects of clenbuterol enantiomers on growth of young male rats - Takashi Kitaura; Shoki Suzuki; William J. Kraemer (Japanese Society of Physical Fitness and Sports Medicine, 2015)
Clenbuterol (CB) is one of the β2-adrenergic receptor agonists with powerful muscle anabolic and lipolytic effects, and is prohibited as a doping drug for athletes. However, it is one of the candidate countermeasures for aging-related diseases. Previously we reported that CB induced muscular hypertrophy, but inhibited the longitudinal growth of bones in young male rats. However, the mechanism of the inhibitory effect on bone growth is not yet clear. CB is manufactured as a 1:1 racemic mixture of 2 isomers of (-)-R and (+)-S enantiomers, and only the (-)-R enantiomer may have pharmacological activity. We examined the effects of two CB enantiomers, (+)-S-CB and (-)-R-CB, on growth of striated muscle and bone in young male rats. Eighteen male Sprague-Dawley rats (8-wk-old) were randomly assigned to a control (CONT, n = 6) and two CB enantiomers groups ((+)-S-CLEB: n=6, (-)-R-CLEB: n=6). Each CB enantiomer of 2 mg/kg body weight was daily administered subcutaneously for 2 weeks. After treatment, heart and the slow-twitch soleus (SOL) and fast-twitch extensor digitorum longus (EDL) muscles and bones were analyzed. The muscle wet weights of SOL and EDL muscles significantly increased in (+)-S-CLEB (HEART: +28%, SOL: +25%, EDL: +28%) and (-)-R-CLEB (HEART: +27%, SOL: +29%, EDL: +35%). Both (+)-S-CB and (-)-R-CB induced striated muscle hypertrophy (heart, SOL, and EDL). Concerning bones, (+)-S-CB induced decreased tibia length (-1.2%) and decreased femur BMD (-5.8%), and (-)-R-CB induced decreased femur BMD (-8.2%). These results show that (+)-S-CB and (-)-R-CB might work differently at times.